Adaptation of Employee Development with Artificial Intelligence Virual Reality in a Power Generation Company - Imron, Ali; Putra, Muhammad Ramadhan; Syahputra, Irwan Edi; PY, Iyus Darmawan; Fadhilah, Amalia Rachmawati Nur (Universitas Bina Sarana Informatika, 2024)
Human resource development and training are essential to improve the quality and skill level of employees. The field of artificial intelligence focuses on developing the ability of computers to accomplish tasks that can currently be completed faster than humans can. To meet higher standards, Power Generation Companies are improving the quality of Virtual Reality (VR) images. VR can be used as a training medium. In addition, it can improve student understanding, information retention, and skills, and provide an immersive and deep learning experience. The purpose of this study is to determine the process of adaptation or application of AI VR in human resource development in the workplace, the contribution of development, and its utilization for work productivity, especially in the power plant company PT PLN Indonesia Power Suralaya banten province.. The method used is descriptive qualitative with a phenomenological approach to the adaptation of AI VR application by explaining the utilization, including the use of design, and AI VR procedures so that it can be adapted in the application of HR development effectively. Reputable national and international journals are used as references for the foundation of the development of this article. The adaptation results in different training modules for employees based on individual skills, job levels, job titles, and desired competencies. The AI tool can then match new projects with employees who have completed training together